Malong the magic cloth - Ordinario, Mary Ann; Atienza, Pepot (Plaridel St., Kidapawan City, Philippines ABC Educational Development Center, 2024)
"What makes the Malong so special? Find out the mystery of the magic cloth as a little boy tells his true-to-life exceptional journey with his family. Children carry a little bit of enchantment all the time. This is the ultimate book for them to discover the magical things around them."--Back cover.
Cover title.
Winner, ASEAN children's book illustrator, best in fiction, ICCRF (International Children's Content Right's Fair) 2017 Chiang Mai, Thailand--Cover.
Keywords: Clothing and dress -- Philippines -- Juvenile fiction; Textile fabrics -- Philippines -- Juvenile fiction; Children's stories, Philippine (English)